2013
DOI: 10.1097/prs.0b013e318290f698
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Inhibitor Reduces Hypertrophic Scarring in a Rabbit Ear Model

Abstract: The introduction of trichostatin A can result in the decreased formation of hypertrophic scars in a rabbit ear model, which is corroborated by evidence of decreased collagen I and fibronectin synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…TSA also inhibited mesangial cell proliferation and the synthesis of collagen and α‐SMA in renal fibrosis (Freidkin et al , ). Furthermore, a recent study using a rabbit ear model showed that TSA led to decreased Col1 and fibronectin synthesis and that it inhibited hypertrophic scar formation (Diao et al , ). These results indicate that HDAC inhibitors could be used to treat fibrotic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…TSA also inhibited mesangial cell proliferation and the synthesis of collagen and α‐SMA in renal fibrosis (Freidkin et al , ). Furthermore, a recent study using a rabbit ear model showed that TSA led to decreased Col1 and fibronectin synthesis and that it inhibited hypertrophic scar formation (Diao et al , ). These results indicate that HDAC inhibitors could be used to treat fibrotic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Russell et al found that epigenetic alteration in keloid fibroblasts was normalized after treatment with TSA [110]. Diao et al injected TSA in hypertrophic scars and observed regression of a pre-established scar [111]. Taken together, these data indicate that topical administration of HDACI could be an effective method to control the overgrowth of skin fibroblasts.…”
Section: Experimental Outcomes Of Hdac Inhibitors In Animal Modelsmentioning
confidence: 99%
“…Typically, these therapies are designed to decrease collagen synthesis (Yamaguchi et al, 2012; Beyer et al, 2013; Diao et al, 2013; Tomcik et al, 2013). …”
Section: Possibilities For Therapeutic Interventionmentioning
confidence: 99%
“…A number of other therapeutic targets have shown promise for the mitigation of mechanically induced fibrosis in preclinical models, including the hedgehog pathway (Horn et al, 2012), extracellular cross-linking enzymes (transglutaminases, lysyl oxidases, and prolyl hydroxylases) (Barry-Hamilton et al, 2010; Kolb and Gauldie, 2011; Olsen et al, 2011), early growth response gene-1 (Yamaguchi et al, 2012), canonical Wnt (Beyer et al, 2013), heat shock protein 90 (Tomcik et al, 2013), histone deacetylase (Diao et al, 2013) and IL-10, which modulates fibrosis by intercepting specific but varied intracellular signaling pathways (Reitamo et al, 1994; Yamamoto et al, 2001; Yuan and Varga, 2001; Nakagome et al, 2006, Occleston et al, 2008; Shi et al, 2013). Although remarkable progress has been made in targeting pro-fibrotic pathways experimentally, clinical translation of these therapies remains an ongoing challenge.…”
Section: Possibilities For Therapeutic Interventionmentioning
confidence: 99%